Elevated plasma EDA fibronectin in primary myelofibrosis is determined by high allele burden of JAK2V617F mutation and strongly predicts splenomegaly progression - Alessandro Malara; Cristian Gruppi; Margherita Massa; Maria Enrica Tira; Vittorio Rosti; Alessandra Balduini; Giovanni Barosi (Frontiers in Oncology, 2022)
In primary myelofibrosis, extra-domain A fibronectin (EDA-FN), the result of alternative splicing of FN gene, sustains megakaryocyte proliferation and confers a pro-inflammatory phenotype to bone marrow cell niches. In this work we assessed the levels of circulating EDA-FN in plasma samples of 122 patients with primary myelofibrosis. Patients with a homozygous JAK2V617F genotype displayed the higher level of plasma EDA-FN. Increased EDA-FN levels were associated with anemia, elevated high-sensitivity C-reactive protein, bone marrow fibrosis and splanchnic vein thrombosis at diagnosis. While no correlation was observed with CD34+ hematopoietic stem cell mobilization, elevated blood level of EDA-FN at diagnosis was a predictor of large splenomegaly (over 10 cm from the left costal margin) outcome. Thus, EDA-FN expression in primary myelofibrosis may represent the first marker of disease progression, and a novel target to treat splenomegaly.